Chemometric optimization and validation of a novel dispersive liquid-liquid microextraction-HPLC method for gliclazide, glibenclamide and glimepiride quantitation in serum samples - Monzón, Celina María (2016)
A dispersive liquid-liquid micro extraction (DLLME) liquid chromatographic method that allows extraction and separation of gliclazide, glibenclamide and glimepiride from serum was developed and optimized with the use of experimental design. The analyzed factors in optimization were type of extracting solvent, extracting solvent volume, dispersing solvent volume, pH and protein precipitation. The selected conditions for DLLME were dichloromethane 100 μL (extracting solvent), acetonitrile 1000 μL (dispersing solvent) and no protein precipitation. This procedure is simple, requires no sophisticated procedures and produces excellent analyte recoveries. Quantitation of glibenclamide, gliclazide and glimepiride in serum samples was carried out by HPLC. This analytical method has been developed and validated, allowing quantitation of the target analytes in presence of atenolol, enalapril and amlodipine besides other serum sample interferents. The chromatographic method is linear, accurate, precise and specific and has the ability to separate the antihyperglycemic drugs from antihypertensive drugs, which are usually found in serum of diabetic patients (LOQs ca. 0.12 μg L-1 for the three analytes).